2006
DOI: 10.1080/09593980600564469
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity with, knowledge, and utilization of standardized outcome measures among physiotherapists in Nigeria

Abstract: Measurement tools that assess changes in patients' clinical status are called outcome measures and their integration into clinical practice promotes objective assessment and evidence-based practice. Healthcare providers' knowledge andfamiliarity with outcome measures are pertinent to their utilization. The purpose of this descriptive survey study was to determine the levels offamiliarity, knowledge and utilization of 16 standardized outcome measures (SOM) among physiotherapists in Nigeria. A 3-part questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
3
17
0
3
Order By: Relevance
“…There were more male than female participants in this study. This implies that there are probably more male than female physiotherapists in Nigeria, and it corroborates the finding of a previous study [12]. Most respondents were working in tertiary and secondary health institutions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were more male than female participants in this study. This implies that there are probably more male than female physiotherapists in Nigeria, and it corroborates the finding of a previous study [12]. Most respondents were working in tertiary and secondary health institutions.…”
Section: Discussionsupporting
confidence: 92%
“…This finding supports the observation that in Nigeria, most physiotherapists work in government facilities, especially university teaching hospitals and state/general hospital. Only a small proportion of physiotherapists in Nigeria practise in primary health care centres, private clinics, or industries [12]. Although physiotherapy practice was introduced into the country in the 1940s, it was only in the 1980s that private physiotherapy services became available, and only a few exist to date.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the practice of physiotherapists in developed countries like New Zealand, Canada, Scotland, England, United States of America and Australia (Copeland et al, 2008). Akinpelu and Eluchie (2006), in their study exploring the familiarity with, knowledge and utilization of standardized outcome measures among physiotherapists in Nigeria, concluded that the use of outcome measures among physiotherapists in Nigeria is limited. While the present study is specific to the use of outcome measures in the treatment of patients with LBP, the study by Akinpelu and Eluchie was on the general use of outcome measures by physiotherapists in Nigeria.…”
Section: Discussionmentioning
confidence: 67%
“…There are studies that explore the usage of OMs in: the United States (Jette et al, 2009;Russek, Wooden, Ekedahl, and Bush, 1997); the United Kingdom (Turner-Stokes and Turner-Stokes, 1997); Canada (Huijbregts, Myers, Kay, and Gavin, 2002;Kay, Myers, and Huijbregts, 2001;Mayo et al, 1993); Australia (Abrams et al, 2006); Nigeria (Akinpelu and Eluchie, 2006); South Africa (Inglis, Faure, and Frieg, 2008); New Zealand (Copeland, Taylor, and Dean, 2008); and other western European countries (Haigh et al, 2001;Torenbeek, Caulfield, Garrett, and Van Harten, 2001), but the extent to which Indian physiotherapists use OMs in their clinical practice has not been studied. There is no published research that explores the use of OMs in India, barriers to their use and its relevance in clinical practice.…”
Section: Introductionmentioning
confidence: 98%